2019
DOI: 10.1080/19942060.2019.1683076
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation projection using a CMIP5 GCM ensemble model: a regional investigation of Syria

Abstract: The possible changes in precipitation of Syrian due to climate change are projected in this study. The symmetrical uncertainty (SU) and multi-criteria decision-analysis (MCDA) methods are used to identify the best general circulation models (GCMs) for precipitation projections. The effectiveness of four bias correction methods, linear scaling (LS), power transformation (PT), general quantile mapping (GEQM), and gamma quantile mapping (GAQM) is assessed in downscaling GCM simulated precipitation. A random fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 66 publications
1
67
0
2
Order By: Relevance
“…It also resulted in the exodus of people from the afflicted villages to the cities [85]. With the projected decrease in annual precipitation by −30 to −85.2% for Syria [86], there may be increased aridity, losses of land productivity, increases in crop water demand and increasing frequency of droughts can increase huge economic loss and more conflicts in Syria.…”
Section: Discussionmentioning
confidence: 99%
“…It also resulted in the exodus of people from the afflicted villages to the cities [85]. With the projected decrease in annual precipitation by −30 to −85.2% for Syria [86], there may be increased aridity, losses of land productivity, increases in crop water demand and increasing frequency of droughts can increase huge economic loss and more conflicts in Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Since the statistical characteristics of the raw historical GCM data differ from the reanalysis data, bias correction of GCM outputs is essential. Multiplicative factors, change factors, delta change approach and quantile mapping are a few examples of simple approaches often used to bias correct the raw GCM output and also as downscaling add on [29,[33][34][35][36]. These approaches have some limitations as well, for example, adopting observed distribution and capturing average statistics of historical time series without focusing on the extremes [37][38][39].…”
Section: Bias Correctionmentioning
confidence: 99%
“…Although it is an effective technique to remove historical biases relative to observed data, it can artificially corrupt the projection of future trends [28]. Furthermore, Homsi et al [29] found that linear scaling (LS) demonstrated the highest capability for precipitation downscaling comparing to three bias correction methods comprising power transformation (PT), general quantile mapping (GEQM) and gamma quantile mapping (GAQM). Saengsawang et al [28] predicted future rainfall under the Representative Concentration Pathway scenarios (RCP2.6, RCP4.5 and RCP8.5) in the UPRB using regression-based downscaling to relate between rainfall depth and climate variables instead of applying raw GCM rainfall data as applied in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…A statistically significant decreasing trend was detected based on runoff data from 925 seagoing rivers including the Mekong River from 1948 to 2004, and yet the impact of human activities on global river runoff was found far less than the effect of climate change [11]. In the prediction of future river runoff variation in Thailand and Malaysia, machine learning models and distributed hydrological models coupled with future climate scenarios are employed and the results show that the variation of forest area induced by land use change is a very influential factor [12][13][14].…”
Section: Introductionmentioning
confidence: 99%